BUDAYA DAN PERDAMAIAN : HARMONI DALAM KEARIFAN LOKAL MASYARAKAT JAWA MENGHADAPI PERUBAHAN PASCA GEMPA - Kartika Herdiyanto, Yohanes; Wahyu Yuniarti, Kwartarini (Universitas Ahmad Dahlan, 2012)
The earthquake that took place in Daerah Istimewa Yogyakarta (DIY)and Central Java on 27 May 2006 gave such tremendous impact toindividual and socials physical and psychological factor, as well as materialdamage. Such alterations were potentially threatening harmonious livingthat has been upheld by the Javanese. Based on the above thought, thisresearch aimed to illustrate the whole psychological overview about theindividuals efforts in countenancing the alterations triggered by theearthquake, using the local wisdom which then brought them to harmonioussocietys life. This study used qualitative method with the ethnography-grounded theoretical approach. One of this researchs essential findingshows that the Javanese still adhering the Javanese local wisdom incountenancing any kinds of post-earthquake alterations. The society wassomewhat took any kinds of conflict, such as the unfair disaster-aiddistributions and the local residence officers corruption acts, passively.Their passive reaction showed that for Javanese maintaining the socialharmonious life is the most essential life purpose; compared if they had toclaim their violated rights.